Implementasi Kebijakan Paud Holistik Integratif dalam Pelayanan Pendidikan Anak Usia Dini di Surabaya - Barnadette Adinda Adel D; Amirul Mustofah; Ika Devy Pramudiana (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study analyzes the implementation of the Holistic Integrative Early Childhood Education (PAUD) policy in Surabaya as a strategic step to improve the quality and equity of PAUD services through intersectoral collaboration. Recognizing the significance of integrating education, health, nutrition, and child protection services, this study aims to analyze implementation strategies, challenges, and local innovations in providing holistic services in PAUD institutions in urban areas. This study applies a qualitative descriptive approach, collecting data through policy document analysis, semi-structured interviews with PAUD administrators, teachers, local officials, and parent representatives, and direct observation at several PAUD institutions. The research findings indicate that policy implementation is carried out through structured socialization, the formation of intersectoral coordination teams, and the provision of additional services such as routine health checks and parenting classes. However, challenges remain, such as uneven facilities and infrastructure among PAUD institutions, differences in teachers' understanding of the holistic integrative concept, and a lack of practical collaboration between PAUD institutions and health or child protection agencies. The study also identified local innovations, such as the use of social media to communicate with parents, enriching teaching materials with local cultural insights, and collaborating with universities to support activities. These findings emphasize that successful policy implementation depends not only on national regulations but also on local leadership skills, stakeholder collaboration, and responsiveness to community needs. Therefore, the study recommends improving ongoing training for educators, providing an adaptive policy framework to support local innovation, and developing digital infrastructure to facilitate more efficient communication and coordination.